Effects of Different Sawdust, Corn Cob, and Rice Husk Substrate Compositions on The Growth And Yield of White Oyster Mushroom (Pleurotus ostreatus) - Asep Ginanjar Arip; Anna Fitri Hindriana; Zaenal Abidin (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
White oyster mushroom (Pleurotus ostreatus) is an edible mushroom widely cultivated due to its nutritional and economic value. This study aimed to evaluate the effect of different substrate compositions of sawdust, corn cobs, and rice husks on the growth and yield of white oyster mushrooms. The experiment was conducted using a Completely Randomized Design (CRD) with four treatments and five replications, resulting in 20 experimental units. Growth parameters observed included stipe length, pileus diameter, fruiting body mass, and the number of fruiting bodies. The results showed that substrate composition significantly affected mushroom growth and productivity. The K2 treatment, consisting of 30% sawdust, 40% corn cobs, and 30% rice husks, produced the best performance in all observed parameters. The higher proportion of corn cobs in the substrate likely provided favorable conditions for mushroom development and yield. In conclusion, a substrate composed of 30% sawdust, 40% corn cobs, and 30% rice husks is recommended for the cultivation of white oyster mushrooms because it promotes optimal growth and productivity.